INNOVATIVE TRICKLING BIOFILTER SYSTEM FOR HOSPITAL WASTEWATER TREATMENT - Manh, Do Van; Hoa, Tran Van; Hoa, Truong Thi; Luong, Hoang (Vietnam Journal of Science and Technology, 2015)
Innovative Trickling biofilter system was applied for wastewater treatment of Danang Rehabilitation – Sanatorium Hospital in this study. The results have shown that the removal efficiencies of COD and BOD5 at loading of 2.5 - 4 kg/m3.day were about 90 %. The inlet concentrations of N-NH4+ and N-NO3- were so high as 33.1 and 26.2 mg/L, respectively. However, the remaining of treated wastewater concentration is 1.4 and 5.2 mg/L, corresponding to the removal efficiencies of 97 and 80 %, respectively. Otherwise, the values of total suspended solid (TSS), phosphates (P), and coliforms were below the limitations of QCVN 28:2010/BTNMT, column A. Resulting from the obtained data in this study, we emphasize that the innovative trickling biofilter system with air supply is appropriate with health-care wastewater treatment and consistent with economic and operating conditions in Vietnam.